Application of mesoporous carbon nitride as a support for an Au catalyst for acetylene hydrochlorination. (2nd October 2015) - Dai, Bin; Li, Xiaoyan; Zhang, Jinli; Yu, Feng; Zhu, Mingyuan
Abstract: To investigate mesoporous carbon nitride (MCN) materials as supports, an Au/MCN catalyst was prepared for acetylene hydrochlorination. Compared with an Au/AC catalyst that uses activated carbon (AC) as the carrier, which is universally applied in industry, the 1% Au/MCN catalyst exhibited excellent catalytic activity, and the initial conversion of acetylene increased relative to the 1% Au/AC catalyst by 53.7%. X-ray photoelectron spectra (XPS) confirmed the presence of nitrogen and carbon species in the Au/MCN catalyst. Transmission electron microscopy (TEM) results indicated that the Au nanoparticles (4.9 nm) were uniformly dispersed and not agglomerated on the surface of the MCN support. Moreover, the analysis results demonstrated that the MCN material not only controlled the Au nanoparticle size, but also was active for acetylene hydrochlorination. Highlights: An Au/MCN catalyst was prepared and used for acetylene hydrochlorination. The Au nanoparticles exhibited considerable catalytic performance in acetylene hydrochlorination. Catalytic performance was influenced by the size of the Au nanoparticles.